Systematic Literature Review : Eksplorasi Etnomatematika pada Aktivitas Pengukuran - Lilis Nurasiah; Hibatul Azizi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the results of ethnomathematical research in the context of measurement activities. The research method chosen in this study was the Systematic Literature Review (SLR) method and was analyzed using the PRISMA method. Data collection was carried out by documenting and reviewing all studies with the Elicit search engine, at the beginning of the search was limited to 499 studies. Then the remaining 150 studies were reviewed and re-screened using inclusion and exclusion criteria, including publication criteria in 2014-2025, resulting in 39 appropriate studies. The results of the analysis showed the consistency of anthropometric measurement units based on body parts such as inches (arm span), depa (arm span), and cubit (forearm). Another emerging consistency is the potential to integrate ethnomathematical measurement practices into formal curricula to enhance contextual learning, although empirical evidence on learning outcomes is still limited. Traditional measurement systems function effectively in the context in question although they are less standardized with accuracy requirements varying by field such as construction using complex unit gradients, while trading emphasizes relative comparison. Measurement practices have traditionally persisted alongside modern standard measurements, this is demonstrated by the parallel use of the two according to the identified mathematical context.